Dieffenbachia Diseases: Identification and Control in Commercial Greenhouse Operations - David Norman (EDIS)
Dieffenbachia is among the top 10 most popular plants produced by commercial foliage growers in Florida. This 4-page fact sheet provides guidelines to identify and treat diseases that may be encountered during the commercial production of Dieffenbachia. Written by David Norman and published by the UF Department of Plant Pathology, October 2011.